Management of Hydramnion in a Holstein Friesian Cow Affected with Prepubic Tendon Rupture - Subramanian , Prakash; Panwar, Shally; Jayaganthan, Ponnusamy; Satheshkumar, Soundarapandian (The Indian Journal of Animal Reproduction, 2026)
A full-term pregnant HF crossbred cow was presented with the history of enlarged abdomen with distended udder for the past five days. Based on the clinical, rectal and ultrasonographic examination, the case was diagnosed as Hydramnion complicated with pre-pubic tendon rupture. By inducing parturition, a dead male cyclops foetus was delivered per vagi num. Animal made an uneventful recovery following treatment.